Enclosure & agricultural improvement in north-west Lincolnshire from circa 1600 to 1850 - Smith, Thomas M. (2012)
This study sets out to establish the link between enclosure and agricultural improvement in a group of parishes in north-west Lindsey, Lincolnshire between the sixteenth century and the mid-nineteenth century. In particular it emphasises the continuity of enclosure history through time, rather than concentrating only on the period of parliamentary enclosure as has often been the case in the past, and on links to agricultural improvement which include land reclamation, draining and warping. It shows that a simple explanation of enclosure in terms of driving up rents and allowing individual farmers to take their own farming decisions, fails to take into account the particular local circumstances of this area. Using a combination of enclosure documents and related material such as glebe terriers, land tax assessments, census materials,the 1801 agricultural returns and estate papers it sets out to show how agricultural improvement transformed both the landscape and the farming techniques in this area. In this process it covers a range of related topics including landownership, population, and the socio-economic structure of the villages of north-west Lindsey. It shows clearly that in this area enclosure is as much as anything associated with land drainage, and with improvements brought about by warping. These processes were interwoven, and separating enclosure out as a single movement underestimates the complexity of the farming arrangements required to ensure the most productive farming in this area.